Studi Faktor Anteseden Turnover Intention - Muhammad Syaifudin; Noor Arifin (Jurnal Dinamika Ekonomi & Bisnis, 2020)
The purpose of this research is to examine and analyze the influence of variables work environment, work stress, and organizational commitment toward turnover intention, study at CV Bagaskara Galih Perkasa. This research uses a quantitative approach. The population and sample in this study were employees of 90 employees, using simple random sampling technique. The data analysis method used is multiple linear regression analysis processed using the IBM SPSS.25 program. The results of the study at the 5% significance level can be concluded that partially (1) the work environment has no effect on turnover intention, (2) work stress has a positive and significant effect on turnover intention, (3) commitment has a negative and significant effect on turnover intention. While simultaneously work environment variables, work stress and organizational commitment have a significant effect toward turnover intention. Based on the R2 test that the three independent variables affect the turnover intention of CV Bagaskara Galih Perkasa employees by 30.5% and the remaining 69.5% are influenced by other variables such as organizational culture, transformational leadership, and perveived organizational support.